Dampak Contract Farming Peternak Sapi Perah Terhadap Ketahanan Pangan Rumah Tangga di Kabupaten Pasuruan - Herlin, Mariana; Ariyani, Aminah Happy Moninthofa; Nugroho, Taufik Rizal Dwi Adi (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
Food security is a strategic issue in agricultural development. Dairy farmers in Tutur Subdistrict, Pasuruan Regency face problems of small-scale livestock ownership, which has an impact on low milk production and income. Limited capital and production facilities cause unstable income, which affects the ability to meet household food needs. Contract farming is a solution to overcome these problems. This study aims to identify the factors that influence farmers' decisions to join contract farming and analyze its impact on household food security. This study was conducted in Tutur District, Pasuruan Regency, with 96 respondents using a multistage sampling method. Data analysis used probit regression to identify participation factors and Propensity Score Matching (PSM) to estimate the impact of contract farming on household food security as measured using the Food Insecurity Experience Scale (FIES). The results showed that the number of livestock and farming experience had a significant effect on farmers' participation in contract farming. PSM analysis shows that contract farming reduces the FIES score by 1.586%. This indicates that contract farming significantly improves household food security.